PERAMALAN PENJUALAN DENGAN DECISION TREE UNTUK OPTIMASI KEUNTUNGAN DI GARMENT NURUL JADID - Anis, Anis Yusrotun Nadhiroh; Nur, Nur Holisah; nafisah, Nafisah Dwi Anggi Yulistina; Syafana, Syarafana Usaimah Mirza (Universitas Lampung, 2025)
Study This aim For predict sale products at Nurul Jadid Garment for optimize profit company through implementation Decision Tree algorithm . Problems faced is fluctuations sales that cause inaccuracy in production and distribution , so that influence efficiency operational and profit . The method used in study This is approach quantitative with Decision Tree algorithm as tool analysis main . Sales data historical collected and processed For identify patterns sale based on attributes like type product , season , and sales volume . Research results show that the Decision Tree model is capable of classify and predict trend sale with level adequate accuracy . Based on results prediction said , the company can plan better production and marketing strategies appropriate target . Conclusion of study This is that use of Decision Tree as tool forecasting sale effective in help taking decision business and can increase profit through efficiency production and reduction excess stock .